Self-efficacy sources and reading comprehension: the mediating role of reading self-efficacy beliefs - Shehzad, Muhammad Waleed; Alghorbany, Ali; Lashari, Sana Anwar; Lashari, Tahira Anwar (Penerbit Universiti Kebangsaan Malaysia, 2019)
The study aimed at identifying the association between Bandura’s four hypothesized self-efficacy sources and reading comprehension by employing reading self-efficacy beliefs as a mediating variable. A correlational research design was used. A total of 351 Saudi EFL learners were selected from eight public universities of Kingdom of Saudi Arabia by employing proportionate stratified random sampling. Two questionnaires including ‘questionnaire for sources of reading self-efficacy’, and ‘reading self-efficacy beliefs questionnaire’, and an IELTS reading comprehension test were used to collect the data. Path analysis by AMOS 23 was utilised in order to test the hypotheses. Findings provided support for the proposed conceptual framework, disclosing that all the four self-efficacy sources were significantly associated with reading self-efficacy beliefs. Also, reading self-efficacy beliefs were significantly associated with reading comprehension. Lastly, reading selfefficacy beliefs mediated the association between self-efficacy sources and reading comprehension. This study offered several theoretical and practical implications for EFL learners, instructors, and educational policymakers on the need of inculcating self-efficacy beliefs among learners to facilitate them in English reading comprehension.